2021
DOI: 10.3390/membranes11060383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Performance of Existing RO Drinking Water Stations in the North Central Province, Sri Lanka

Abstract: Reverse osmosis (RO) drinking water stations have been introduced to provide safe drinking water for areas with prevailing chronic kidney disease with unknown (CKDu) etiology in the dry zone of Sri Lanka. In this investigation, RO drinking water stations established by community-based organizations (CBO) in the North Central Province (NCP) were examined. Water samples were collected from source, permeate, and concentrate in each station to determine water quality and performance. Furthermore, the operators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Thus, advanced water treatment technologies such as RO, nanofiltration (NF), and electrodialysis reversal (EDR) are required to purify these groundwaters with high mineral content. RO membrane technology has been already implemented in many villages of these regions, , . RO systems can handle feedwater with higher EC and hardness to produce drinkable water with lower mineral content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, advanced water treatment technologies such as RO, nanofiltration (NF), and electrodialysis reversal (EDR) are required to purify these groundwaters with high mineral content. RO membrane technology has been already implemented in many villages of these regions, , . RO systems can handle feedwater with higher EC and hardness to produce drinkable water with lower mineral content.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, fluoride removal should be the main focus in this region. This can be easily achieved by the RO filtrations because RO technology shows excellent removal of fluoride and HCO 3 – ions in this type of groundwater. , However, this groundwater does not need an advanced and expensive purification technology with a higher salt rejection capability, because the total mineral content (EC < 500 μS/cm) was significantly lower in the shallow groundwater in this region. If RO filtration is used, produced drinking water will have quite lower mineral content (EC < 20 μS/cm) which could lead to mineral deficiencies due to its higher mineral rejection rates (>96.6%); thus, a post mineral addition process should be carried out.…”
Section: Resultsmentioning
confidence: 99%
“…reported that the decrease in Ca +2 rejection was due to the greater permeability of Ca +2 through the membrane. Moreover, Indika et al [36] . found that when the ion concentration increases, especially the Ca +2 and Mg +2 ions, more divalent ions adhere to the membrane surface and cover a considerable area of the membrane surface.…”
Section: Resultsmentioning
confidence: 99%
“…[25] In addition, Gallab et al [34] reported that the decrease in Ca + 2 rejection was due to the greater permeability of Ca + 2 through the membrane. Moreover, Indika et al [36] found that when the ion concentration increases, especially the Ca + 2 and Mg + 2 ions, more divalent ions adhere to the membrane surface and cover a considerable area of the membrane surface. Furthermore, Agnesson et al [37] claimed that fouling modified the membrane surface properties, thus affecting the ion rejection pattern.…”
Section: Chemistryselectmentioning
confidence: 99%
“…In addition, the use of RO also increases the operation cost of the water treatment system. 11 Functionalized activated carbon has been used as a water filtering medium for purification of drinking water for many years. It is widely used for the removal of contaminants in water due to its high capacity for adsorption of such compounds, arising from its large surface area and porosity.…”
Section: Introductionmentioning
confidence: 99%